Use of Virtual Tour Media Based on Lebak Local Products in Social Studies Learning in Elementary School - Ginanjar, Ajeng; Aim Abdul Karim; Kokom Komalasari; Erlina Wiyanarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The virtual tour media based on Lebak local products is designed as an alternative learning media in social studies subjects. Given the situation and conditions at school show that teachers still teach naturally and have not creatively used learning media. The purpose of writing this article is to describe the use of virtual tour media based on Lebak local products in social studies learning so that learning is more meaningful and achieves goals. This research uses quantitative methods with survey techniques and observations of 100 respondents. The data collection technique used a questionnaire distributed to teachers. The results of this study indicate that the use of virtual tour media based on Lebak local products can encourage meaningful learning and achieve learning objectives such as describing Lebak local products including batik cloth, Baduy dyed and woven cloth, crafts, palm sugar and emping as part of the natural wealth and potential of the area where students live, thus encouraging active participation, creativity of students in social studies learning.